Collecter et archiver en territoire transfrontalier - Sandrine Teixido (In Situ)
Oral music in Alsace has recently developed in interaction with other aesthetics and through cultural policies that make the territory a criterion for action. We will consider a diversity of collecting practices and scales, focusing in particular on the case of Mulhouse, which has a long history of migration that enables us to understand the interrelationship between different musical aesthetics. We will then look at the claimed links between music and the Alsace region, and finally extend our discussion to the Upper Rhine, questioning the relevance of this scale for understanding the historical dimension of cultural exchange in the Rhine area. This will lead us to examine the possibility of grasping in the present the links between territory and becoming a musician.